Primary gold mineralization in the Pre-Cambrian and lower Paleozoic rocks, Lungri Khola region, Rolpa district - Joshi, P. R. (Journal of Nepal Geological Society, 1991)
Primary gold mineralization occurring in the Lungri Khola region is observed in the Pre Cambrian green schist facies and Lower Paleozoic micaceous marble and limestone. The Pre-Cambrian green schist facies comprising mainly of sericite and chloritic quartzite, chlorite schist, quartz-chlorite schist, chlorite phyllite and schistose pebble beds include a discontinuous auriferous zone which persists laterally for about 30 km extension from the Gajul khola in the west to the upper reaches of Gam khola in the east. The auriferous host rocks are found confined close to the contact with the overlying Lower Paleozoic carbonates. Eight distinct auriferous hosts are encountered in the Pre-Cambrian green schists facies. Occurrence of auriferous host in the Lower Paleozoic limestone and marble is rather irregular and insignificant So far minor quartz-carbonate veins have indicated the presence of gold. Finely disseminated gold with minor amount of pyrite, chalcopyrite and rarely arsenopyrite occurs in the above hosts. Visible gold ranging from 0.08 to 2 mm dimension has been recovered. Gold content of upto 6.7 gm/ton has been recorded but in general they show 0.1 gm/ton gold which is significantly 30 to 60 times higher in magnitude than the background value. Depending upon the type of the hosts, three possible models, namely (1) volcanogenic (2) hydrothermal and (3) syn-sedimentary, could be suggested for the origin of the primary gold mineralization which has later undergone remobilisation after the initial deposition.